Konsep penerimaan menurut al-Ghazali dan Maslow: Satu kajian perbandingan [Receiving concepts by al-Ghazali and Maslow: One of comparative study] - Norhashimah, Yahya; Syed Hadzrullathfi, Syed Omar (2019)
The necessity of life is a very important thing for mankind to continue to live well. Usually in human endeavor to meet the needs of life it is driven by the desire to achieve self-satisfaction. The concept of the human will proposed by Abraham Maslow is to meet the necessities of life alone. However, the elements of self-satisfaction, happiness and the concept of acceptance in the human person cannot be fully achieved according to that concept. However, the concept of human will presented by alGhazali especially in meeting the needs of life is seen to encompass these three elements that are needed by man. Therefore, the positioning of the concept of the will associated with the necessity of living to attain the element of acceptance must be possessed by the individual and is a priority to be emphasized in academic research. This qualitative study using the content analysis method found that al-Ghazali's approach focuses more on the aspects of faith and revelation in meeting the needs of life in line with human needs. Although Maslow's thinking on living needs is more systematic by presenting a hierarchy of living needs for humans, the concepts presented to meet those needs are more focused on the faculties and passions. Therefore, an analysis of the differences and similarities between these two aspects of acceptance should be made to produce a more effective corpus of Islamic psychology.